Academic Procrastination among Students: Psychological Factor Contributions of Academic Stress, Self-Efficacy, and Self-Control - Iszanul Dani Nurdiansah; Didit Darmawan (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2025)
One of the most prevalent issues in educational environments is deliberate academic procrastination on school-related assignments.  Students' academic performance may suffer due to this behavior, which could impede their achievement.  Examining how academic stress, self-efficacy, and self-control affect students' propensity to put off academic tasks is the goal of this study.  This quantitative study was conducted on ninth-grade pupils at a Surabaya state madrasah. A total of 147 students participated, selected through purposive sampling. Data collection was conducted using Google Forms distributed through the class WhatsApp group. To analyze the influence of independent and dependent variables, SPSS version 26 was used to analyze multiple linear regression. The study's findings suggest that neither academic stress nor self-efficacy substantially impacts students' academic procrastination.   Self-control has a statistically significant impact on academic procrastinating behavior.  Academic procrastination was significantly influenced by academic stress, self-efficacy, and self-control. Academic procrastination is thus significantly predicted by self-control.  At one of the state madrasahs in Surabaya, students' academic procrastination is not primarily predicted by academic stress or self-efficacy.